2009
DOI: 10.1001/archgenpsychiatry.2009.19
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Amygdala Volume and Joint Attention in 2- to 4-Year-Old Children With Autism

Abstract: Context Cerebral cortical volume enlargement has been reported in 2- to 4-year-olds with autism. Little is known about the volume of sub-regions during this period of development. The amygdala is hypothesized to be abnormal in volume and related to core clinical features in autism. Objective To examine amygdala volume at 2 years with follow-up at 4 years of age in children with autism and to explore the relationship between amygdala volume and selected behavioral features of autism. Design Longitudinal mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
186
2
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(217 citation statements)
references
References 55 publications
(69 reference statements)
17
186
2
12
Order By: Relevance
“…37,[84][85][86][87][88][89] Enlargement has been noted in the frontal and temporal lobes 37,90 and in specific subcortical structures, such as the amygdala. 36,91 Enlargement has been observed in children as young as age 12 months and may be accompanied by an increase in extra-axial fluid. 87 Head circumference, which is a crude proxy for brain size, is generally consistent with brain enlargement in ASD, 84 although a recent review has raised questions as to whether ASD-related increases in head circumference have been largely driven by comparison with outdated population-based norms.…”
Section: Early Neurobiological Processesmentioning
confidence: 99%
“…37,[84][85][86][87][88][89] Enlargement has been noted in the frontal and temporal lobes 37,90 and in specific subcortical structures, such as the amygdala. 36,91 Enlargement has been observed in children as young as age 12 months and may be accompanied by an increase in extra-axial fluid. 87 Head circumference, which is a crude proxy for brain size, is generally consistent with brain enlargement in ASD, 84 although a recent review has raised questions as to whether ASD-related increases in head circumference have been largely driven by comparison with outdated population-based norms.…”
Section: Early Neurobiological Processesmentioning
confidence: 99%
“…Sin embargo, la amígdala de individuos autistas con edades entre 7 a 12 años, alcanza el tamaño adulto antes de la adolescencia, mientras que los niños de desarrollo típico presentan un crecimiento progresivo de la amígdala hasta la adolescencia. En consonancia con esta investigación Mosconi et al (2009) observaron la ampliación bilateral de la amígdala, en una amplia gama de muestras de niños con TA de 2 años de edad, que persistió hasta los 4 años. Por su parte, Sparks et al (2002) también observaron mayores volúmenes de la amígdala, en niños con TA de 3 a 4 años de edad.…”
Section: Características Neuroanatómicasunclassified
“…Recientemente, Murphy et al (2012) a través de imáge-nes de resonancia magnética estructural, realizaron comparaciones del volumen de la amígdala de 32 individuos con SA (12-47 años) y 32 controles sanos, quienes no difirieron significativamente en la edad o el coeficiente intelectual. Los hallazgos encontrados apoyaron informes previos de la ampliación de amígdala en niños pequeños con TEA Schumann et al, 2004Schumann et al, , 2009Mosconi et al); sin embargo, encontraron que en varones adolescentes y adultos con SA, la amígdala sigue siendo significativamente mayor, en comparación con los controles de la misma edad. Además, observaron que el desarrollo de la amígdala parecía ser diferente entre los grupos.…”
Section: Características Neuroanatómicasunclassified
“…Changes in the function and neuropathology of the amygdala have long been known in autism (Baron-Cohen et al, 2000). Postmortem studies show cell packing changes (Bauman and Kemper, 2005) and size changes in MRI studies have been observed (Aylward et al, 1999;Schumann et al, 2009) which can be correlated with the ability to engage in joint attention (Mosconi et al, 2009). fMRI activation when looking at faces is different in autism (Critchley et al, 2000).…”
Section: Neuroendocrine Hypothesismentioning
confidence: 99%